Aplikasi Informasi Pendaftaran Member dan Penjualan Merchandise pada Komunitas Manchester City Supporters Club Indonesia Chapter Purwokerto - Ainizar, Muhammad Alif; Nisa, Khoirun (Jurnal Nasional Teknologi Informasi dan Aplikasnya, 2023)
Community is a group of people who come together and have the same interests and preferences. There are many communities in the world, one of which is the Manchester City Supporters Indonesia Chapter Purwokerto Community. This community has a passion for Manchester City Football Club. With a large number of members, this community often holds events and member registration. With this in mind, this community has created a web-based application where prospective members and members can see up to date information in the application as well as prospective members can register online in the application. The application also sells community-owned products and these products can be used during community events. With the application entitled Information Application, Member Registration and Website-based Merchandise Sales, it is hoped that members can register, view up to date information and buy community merchandise in the application. Keywords:  Chapter Purwokerto, Member Registration, Manchester City Supporters Indonesia Chapter Purwokerto Community, Website-based Merchandise Sales